2018
DOI: 10.18632/aging.101599
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Nox4 interaction with prelamin A is associated with nuclear redox control of stem cell aging

Abstract: Mesenchymal stem cells have emerged as an important tool that can be used for tissue regeneration thanks to their easy preparation, differentiation potential and immunomodulatory activity. However, an extensive culture of stem cells in vitro prior to clinical use can lead to oxidative stress that can modulate different stem cells properties, such as self-renewal, proliferation, differentiation and senescence. The aim of this study was to investigate the aging process occurring during in vitro expansion of stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…They argued that mtROS activates Nrf2 based on the fact that NOX4 and SOD2, but not NOX2 and SOD1, are induced by AES. Although different NOX4 subcellular localization has been reported, including in the nucleus and endoplasmic reticulum [76,77], NOX4 has been shown to mainly localize in mitochondria, especially in the heart Metabolic stress, such as caloric restriction and exercise, causes a decline in ATP levels and an increase in the NAD + /NADH ratio that is sensed by downstream pathways that promote mitochondrial function and increase ATP synthesis [50,55]. An increase in AMP/ATP activates AMPK, which induces mitochondrial biogenesis via PGC1α activation and enhances autophagy via mTOR inhibition.…”
Section: Role Of Mtros and Nrf2 In Mediating The Healthy Effect Of Exmentioning
confidence: 99%
See 1 more Smart Citation
“…They argued that mtROS activates Nrf2 based on the fact that NOX4 and SOD2, but not NOX2 and SOD1, are induced by AES. Although different NOX4 subcellular localization has been reported, including in the nucleus and endoplasmic reticulum [76,77], NOX4 has been shown to mainly localize in mitochondria, especially in the heart Metabolic stress, such as caloric restriction and exercise, causes a decline in ATP levels and an increase in the NAD + /NADH ratio that is sensed by downstream pathways that promote mitochondrial function and increase ATP synthesis [50,55]. An increase in AMP/ATP activates AMPK, which induces mitochondrial biogenesis via PGC1α activation and enhances autophagy via mTOR inhibition.…”
Section: Role Of Mtros and Nrf2 In Mediating The Healthy Effect Of Exmentioning
confidence: 99%
“…They argued that mtROS activates Nrf2 based on the fact that NOX4 and SOD2, but not NOX2 and SOD1, are induced by AES. Although different NOX4 subcellular localization has been reported, including in the nucleus and endoplasmic reticulum [76,77], NOX4 has been shown to mainly localize in mitochondria, especially in the heart [78][79][80]. Indeed, several beneficial effects of exercise in the vasculature and skeletal muscle, such as increased physical activity, are diminished in NOX4-knockout mice [81].…”
Section: Role Of Mtros and Nrf2 In Mediating The Healthy Effect Of Exmentioning
confidence: 99%
“…In MSCs, alterations in lamin A protein have been described to disrupt nuclear organization, leading to the sequestration of transcription factors to the nuclear periphery [ 115 , 116 , 117 , 118 ]. This pathological entrapment of transcription factors leads to an impaired homeostasis in MSCs, affecting their fate [ 116 , 119 ]. This is the case of PPARs, which are essential regulators of MSCs’ differentiation [ 120 ].…”
Section: Lamin A/c and Mscsmentioning
confidence: 99%
“…Comprehensive experimental studies over the past decade have shown OS can impair stem cells' redox homeostasis in hematopoietic, neural, and muscle stem cell compartments [100]. Stem cells are involved in preserving tissue homeostasis and the repair of damaged DNA through replacing damaged/lost cells; thus, they play an important role for functional tissue and organ maintenance [101]. Therefore, the regulation of balance between quiescence, self-renewal, and differentiation is crucial for stem cell functioning during early development and cell homeostasis [100102].…”
Section: Discussionmentioning
confidence: 99%
“…The response mechanism of stem cells on OS is not well recognized, but accelerated telomere shortening, increased double-stranded DNA breaks, and nuclear A-type prelamin accumulation, followed by stem cell senescence or premature aging and cell death, have been reported [103]. An important role of A-type prelamins, i.e., the proteins responsible for the structural and functional integrity of the cell nucleus, is the ability to modulate intracellular redox homeostasis [101]. The experimental study of aging processes during in vitro expansion of stem cells from amniotic fluids (hAFSCs cultures) by Casciaro et al showed low levels of intracellular ROS prevented nuclear A-type prelamin accumulation and Nox4 nuclear activity towards ROS production [101].…”
Section: Discussionmentioning
confidence: 99%